BIOLOGI REPRODUKSI TUMBUHAN KAMBOJA (Plumeria rubra) - Hendriawan; Sulistia Febriani; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Frangipani (Plumeria rubra) is a tropical ornamental plant that plays an important role in landscape aesthetics and ecological interactions in tropical environments. This study aims to comprehensively analyze the reproductive biology of Plumeria rubra, including its generative and vegetative mechanisms. The method used in this study is direct observation combined with descriptive analysis. The results indicate that generative reproduction involves complex pollination mechanisms influenced by floral morphology, pollinator interactions, and environmental factors. However, fruit and seed formation are relatively rare under natural conditions. In contrast, vegetative reproduction through stem cuttings is highly efficient and widely utilized due to its rapid growth and genetic stability. From a conservation perspective, this species is not classified as threatened due to its adaptability and widespread cultivation. These findings highlight the dominance of vegetative propagation in maintaining population sustainability of Plumeria rubra in both natural and artificial ecosystem.